A rare ocular complication of mumps: Kerato-uveitis - TOKER, AYŞE EBRU (TAYLOR & FRANCIS INC, 2005)
Purpose: To report a child who developed kerato-uveitis associated with mumps infection. Methods: A prospective study of a child who was observed at the Department of Ophthalmology, Marmara University, Faculty of Medicine, during spring 2003. Results: An 11-year-old male patient noticed decreased vision in his left eye. His right eye was completely normal. Visual acuity was perception of hand movements in the left eye. Ocular examination revealed ciliary injection and diffuse hyperemia of the conjunctiva, interstitial keratitis characterized by prominent stromal infiltrates and edema, folds in the Descemet's membrane, and microcystic epithelial edema in his left eye. The patient had been diagnosed as having mumps 10 days previously by a pediatrician. Complete recovery of the keratitis occurred on the 10th day of topical steroid treatment. Conclusions: Keratitis and/or iritis are rare complications of mumps. Corneal involvement is characterized by unilateral and painless interstitial keratitis that may cause a significant decrease in vision. Keratitis resolves with treatment and does not have any sequelae.
Keywords: kerato-uveitis; mumps; children